2016
DOI: 10.1242/jcs.183053
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FAM3D as a new endogenous chemotaxis agonist for the formyl peptide receptors

Abstract: The family with sequence similarity 3 (FAM3) gene family is a cytokine-like gene family with four members FAM3A, FAM3B, FAM3C and FAM3D. In this study, we found that FAM3D strongly chemoattracted human peripheral blood neutrophils and monocytes. To identify the FAM3D receptor, we used chemotaxis, receptor internalization, Ca 2+ flux and radioligand-binding assays in FAM3D-stimulated HEK293 cells that transiently expressed formyl peptide receptor (FPR)1 or FPR2 to show that FAM3D was a high affinity ligand of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…FAM3D is part of a family of cytokines containing four genes (FAM3A, FAM3B, FAM3C and FAM3D) that is mainly expressed in highly proliferative tissue such as placenta and the gastrointestinal tract [28]. It has been suggested to play a role in cell proliferation, and functions as an activator of the ERK1/2 and p38MAPK signaling pathways [29]. Finally, the third highly significant CpG (cg03472655) was located in the gene SH2D5 (SH2 Domain Containing 5 protein) which is an adaptor-like protein expressed mainly in the brain [30].…”
Section: Discussionmentioning
confidence: 99%
“…FAM3D is part of a family of cytokines containing four genes (FAM3A, FAM3B, FAM3C and FAM3D) that is mainly expressed in highly proliferative tissue such as placenta and the gastrointestinal tract [28]. It has been suggested to play a role in cell proliferation, and functions as an activator of the ERK1/2 and p38MAPK signaling pathways [29]. Finally, the third highly significant CpG (cg03472655) was located in the gene SH2D5 (SH2 Domain Containing 5 protein) which is an adaptor-like protein expressed mainly in the brain [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although several previous reports have shown that FAM family members are involved in some biological functions, including the regulation of leukocyte adhesion, migration 3 , 26 , phagocytosis 3 , vascular inflammation 27 , and microglia/macrophage polarization 28 , studies on the functional role of FAM19A5 are limited. In this study, we demonstrated that FAM19A5, an endogenous brain-specific chemokine, strongly inhibited RANKL-induced osteoclast generation, suggesting a novel inhibitory functional role of FAM19A5 in osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, a new host-derived chemotaxis agonist FAM3D, for the FPR1 and FPR2 was identified [ 135 ]. FAM3D, a cytokine-like protein, is constitutively expressed in the gastrointestinal tract with significant induction in dextran sulfate sodium (DSS)-induced colitis [ 135 ]. FAM3D was found to strongly attract the chemotaxis of human peripheral blood neutrophils and monocytes.…”
Section: Agonists For the Formyl Peptide Receptorsmentioning
confidence: 99%